A Study of Individual‐Level Social Capital and Health Outcomes: Testing for Variance between Rural and Urban Respondents. (11th December 2013) - Beaudoin, Christopher E.; Wendel, Monica L.; Drake, Kelly
Abstract This study examines associations between social capital and health outcomes with data from the 2010 Brazos Valley Health Survey (Texas) (N = 3, 176). Multivariate adjusted logistic regression analysis demonstrated that poor and fair health status was inversely predicted by both high trust (adjusted OR = .67 [CI = .50–.92]) and high informal social ties (adjusted OR = .68 [CI = .49–.94]), as well as being predicted by the interaction of urban‐rural and community participation (adjusted OR = 1.20 [CI = 1.02–1.40]). Mental distress was inversely predicted by high trust (adjusted OR = .51 [CI = .29–.89]) and the interaction of urban/rural and informal social ties (adjusted OR = .77 [CI = .61–.97]). Thus, whereas social capital poses general benefits in regard to improving health status and mental distress, the former benefits are greater for rural respondents, while the latter benefits are greater for urban respondents.